Primary bilateral malignant melanoma of the lower limbs - Serena Lembo; Matteo Megna; Paolo Maddalena; Ambra Monfrecola; Anna Balato; Antonello Baldo (Dermatology Reports, 2011)
Malignant melanoma is the eighth most common cancer in European women. Its incidence is increasing rapidly and it has been demonstrated that this is related to sun exposure. Although few cases of bilateral uveal or choroidal melanoma are described in literature, there are no cases reporting bilateral cutaneous malignant melanoma. We report a singular case of a 43-year-old woman with two primary bilateral melanomas localized on the flexural surface of both legs.